Pemikiran Pendidikan Islam Ismail Raji al-Faruqi - Ahmad Rudi Alpata (Tamilis Synex: Multidimensional Collaboration, 2024)
This study aims to deeply analyze Ismail Raji al-Faruqi's thoughts on the concept of Islamic education, rooted in the principle of tawhid (divine unity). Utilizing a philosophical and historical approach, this research explores al-Faruqi's ideas on the unity of knowledge, humanity, and truth as the foundation of Islamic education. Data were collected through library research from various primary and secondary sources. The findings reveal that al-Faruqi rejects the dichotomy between religious and worldly sciences and emphasizes the importance of integrating revelation and reason in the education system. Al-Faruqi's ideas on the Islamization of knowledge provide a solution to address the crisis in modern science and offer a holistic paradigm for Islamic education. This research contributes to the development of Islamic education curricula that are relevant to the challenges of the contemporary era.